Pengaruh Perceived Value, Service Quality dan Brand Image Terhadap Minat Beli Tiket Pesawat pada PT Garuda Indonesia - Balkhis, Kamelia; Widiyanti, Marlina; Saggaff Shihab, Muchsin; Maulana, Ahmad (Green Publisher Indonesia, 2024)
This research was conducted to determine the influence of perceived value, service quality and brand image on the interest in buying air tickets at PT Garuda Indonesia. The population in this study is all customers who purchase Garuda Indonesia flight tickets in the city of Palembang in 2024. The sample used in this study was 100 respondents using the purposive sampling method. The results of multiple linear regression analysis show that perceived value, service quality and brand image have a positive and significant effect on buying interest. Perceived value, it is expected for PT Garuda Indonesia to be able to accelerate the duration of the process of refunding funds to consumers. Service quality, it is hoped that PT Garuda Indonesia will provide information to consumers if there is a change in information. Brand image, it is hoped that PT Garuda Indonesia can consider conducting events such as exhibitions which also need to be carried out in several cities in Indonesia.